Analysis of a Four-Legged Robot Kinematics during Rotational Movements of Its Body - M. J. Fernando; G. R. Saypulaev; M. R. Saypulaev (Advanced Engineering Research)
Introduction. Walking robots are widely used in industry due to their unique capabilities for moving on uneven and complex surfaces. To provide high precision in controlling their movement, it is required to develop mathematical models and algorithms for planning the robot movement along various trajectories. A key aspect of the motion control system of walking robots is the planning of their leg movements. Despite significant advances in the field of modeling the kinematics of quadruped robots, existing scientific publications do not provide a complete kinematic model for robots similar to the Mini Cheetah. This research was aimed at the development of a kinematic model of a quadruped robot based on Mini Cheetah, as well as the formulation of recommendations for optimizing its gait to provide rotation around various axes. The creation of such a model will improve the smoothness and accuracy of the robot movements, which, in turn, will increase its efficiency under real production conditions.Materials and Methods. The process of constructing a kinematic model of the robot was based on the use of formulas for the geometry of spatial motion of solids. To test the efficiency of the proposed algorithms for moving the robot legs when performing rotational movements of its body, numerical modeling of the robot kinematics was used. Numerical calculations were performed using the Wolfram Mathematica package.Results. The laws of changing the endpoints of the robot legs during its rotation around the vertical axis were proposed. The conducted numerical modeling of the robot kinematics covered the rotation of the body at the course, roll and pitch angles. Based on the simulation results, it was established that the dependences of the rotation angles of the leg links were periodic functions. The considered rotational movements of the robot platform could take place without the occurrence of singular configurations.Discussion and Conclusion. The results of numerical modeling of the robot platform rotation movements confirmed the operability of the proposed leg transfer plan, which allowed for smooth movement of the robot body and avoidance of singular configurations. The resulting kinematic model can be used to control the robot motion at the kinematic level when moving along curvilinear trajectories. As a prospect for further research, it is worth highlighting the development of a mathematical model of the dynamics of a four-legged robot, as well as the creation of laws for controlling its movement at a dynamic level. This will significantly expand the functionality of the robot and increase its efficiency under various operating conditions.